Weierstrass semigroups from cyclic covers of hyperelliptic curves - Cotterill, Ethan, 1979- (2023)
Agradecimentos: We thank Joe Harris for illuminating conversations, and the anonymous referee for comments that have helped us improve the exposition. Fernando Torres invited the first author to speak in Campinas on this topic in early 2020, and sadly left us before this project’s completion. We dedicate this paper to his memory